Investigating the Effectiveness of a Virtual-Reality-Based Mindfulness Intervention on Internet Gaming Disorder - Selma Tvrtković-Hasandić; Pınar Ünal-Aydın (Behavioral Sciences)
Novel treatment approaches for Internet Gaming Disorder (IGD) include the use of mindfulness and technology-based interventions. Mindfulness has been shown as a protective factor against IGD, but the treatment dropout rates are high due to long sessions and treatment duration. Pathological gamers show approach bias towards technological gadgets, and the inclusion of Virtual Reality has been effective in IGD treatment. Due to the effectiveness of mindfulness and the attractiveness of VR, a combined intervention could decrease treatment time and willingness for treatment. Therefore, the aim of this study was to examine the effectiveness of a brief VR-based mindfulness intervention on IGD symptomatology. Nine participants meeting the IGD symptom criteria, ten recreational game users, and eight healthy controls without a gaming history participated in the study. The intervention consisted of four weekly 20-min-long Attentional Focus Mindfulness sessions. The results indicate a significant reduction in IGD symptoms and weekend gaming time in the treatment group. Despite the small sample size in the treatment group (n = 9) and lack of randomization, the findings constitute a valuable starting point. As a cost- and time-effective intervention, this approach could reduce dropout rates and increase treatment adherence, especially in younger gamers. Additional studies with a larger sample size, randomization, and a longitudinal approach are needed to further validate the found results.